MANAJEMEN RISIKO PELAKSANAAN PEMBANGUNAN SISTEM PENGOLAHAN AIR LIMBAH TERPUSAT KOTA DENPASAR TAHAP II (JARINGAN AIR LIMBAH PEDUNGAN) - I Gusti Agung Adnyana Putera; Kadek Diana Harmayani; I Gede Indrajaya Putra (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
ABSTRACT: Denpasar Centralized Waste Water Treatment System Project Phase II (Pedungan Waste Water Network) was conducted in Fiscal Year 2015. The project has been undertaken to improve the service of domestic waste water from households, boarding houses, restaurants, hotels, as well as villas. Processing system used is the centralized piping system and the management of the local system IPLT (Faecal Matter Processing Installation) as well as expanding the waste water pipe network in the city of Denpasar. IPLT development is a project that is claimed as the project's first stool processing engine technology in Bali. Based on this, there is a need to study of the risks that occur during the construction of the project. The research was conducted through interviews along with personnel experience and expertise, manufacture and distribution of the questionnaire, doing a test from the result of questionnaire with test the validity and reliability risks that arise in the implementation of this project. Risks are obtained in this study a number of 71. The distribution of risk acceptability in the project as much as 8 (11.27%) risk (less precise drawings, project specifications and addendum provided by the owner), including unacceptable, 50 (70.42%) risk ( quality concrete Pile Anchorge that does not comply with the specifications approved) including undesirable, 9 (12.68%) risk (operational and overhead costs are high) including acceptable, 4 (5.63%) risk (the use of the funds out of contract ) including negligible. Risk mitigation is only given to major risk include risk unacceptable and undesirable risk. Based on the results of the risk management, implemented regulations on ownership of risk (risk ownership) against perpetrators (project owners, consultants, planners, consultants and contractor supervision) involved in the implementation of Denpasar centralized wastewater treatment system project.